European Parliament after the Treaty of Lisbon Entered into Force and Elections in June 2009 (Economic and Political Thought, 2010)
The European Parliament is one of the major and most important organsof the European Union and Communities and its role and participationin those institutions’ decision making process increases systematically,simultaneously with every successive reforming treaty entering into force.The present article is an attempt to present the European Parliament afterthe latest great events in the European Union, i.e. the election of June 2009and 1 December 2009, when the Treaty of Lisbon came into force.The author attempts to answer numerous questions that are asked inconnection with the last European election and the Treaty of Lisbon. He triesto show how this election and the Treaty of Lisbon changed the image of theEuropean Parliament and strengthened its competence. He proposes manyinteresting theses, including one that the European election of 2009 togetherwith the treaty of Lisbon are a turning point not only in the history of theEuropean Parliament but also the history of the European integration andits effect: the European Union. In the article, there are many references toPoland and its experiences after the accession to the European Union in 2004and in the European Parliament. The author proves that today the Poles aresatisfied with the European Union membership and feel more confident inthe European Parliament and in all the European Union salons.